2019
DOI: 10.1161/hypertensionaha.118.12109
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Composition and Blood Pressure

Abstract: Animal models support a role for the gut microbiota in the development of hypertension. There has been a lack of epidemiological cohort studies to confirm these findings in human populations. We examined cross-sectional associations between measures of gut microbial diversity and taxonomic composition and blood pressure (BP) in 529 participants of the biracial (black and white) CARDIA study (Coronary Artery Risk Development in Young Adults). We sequenced V3-V4 regions of the 16S ribosomal RNA marker gene using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
186
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(230 citation statements)
references
References 49 publications
20
186
4
1
Order By: Relevance
“…Abundant evidence has demonstrated an association between gut dysbiosis and hypertension (Li et al, ; Mell et al, ; Sun et al, ; Toral et al, , ; Yang et al, ). Our results are consistent with the main features of dysbiotic microbiota described in SHR (Toral et al, , ; Yang et al, ; Yang et al, ): (a) a reduced richness and diversity, (b) an increased F/B ratio, and (c) a reduction in acetate‐ and propionate‐producing bacteria, with higher proportion of lactate‐producing bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abundant evidence has demonstrated an association between gut dysbiosis and hypertension (Li et al, ; Mell et al, ; Sun et al, ; Toral et al, , ; Yang et al, ). Our results are consistent with the main features of dysbiotic microbiota described in SHR (Toral et al, , ; Yang et al, ; Yang et al, ): (a) a reduced richness and diversity, (b) an increased F/B ratio, and (c) a reduction in acetate‐ and propionate‐producing bacteria, with higher proportion of lactate‐producing bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that the normal gut microbiota may influence BP. A direct association between gut microbiota and hypertension in both animal models and humans has been described (Yang et al, ; Kim et al, , Toral et al, , , Sun et al, ). In contrast, Karbach et al () showed that BP was not different between germ‐free and conventionally raised mice, which is consistent with previous observations describing no effect on BP after dramatic reduction in faecal microbial biomass induced by antibiotic treatment (Pluznick et al, ).…”
Section: Introductionmentioning
confidence: 98%
“…This is the case of patients with anti-hypertensive treatment, which included in many cases a complex of different angiotensin II receptor blockers, angiotensin-converting enzyme inhibitors, diuretics, calcium channel blockers, and β-1 adrenergic blockers. Although there are no human studies that specifically address the possible effect of this mixture of anti-hypertensive drugs on the gut microbiota [48], a recent study shows that the angiotensin receptor blocker losartan exerted anti-hypertensive effects, at least partially, by modulating the gut microbiota of spontaneously hypertensive rats [49]. Nevertheless, we speculate that the significant structural variability of anti-hypertensive drugs might prevent the elucidation of common mechanisms of action (either direct or indirect) on the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension is among the most prevalent risk factors for cardiovascular events such as stroke and myocardial infarction. Up to present date, an ever‐increasing number of studies have shown a link between gut microbial signatures and hypertension in both animal models and human patients . In general, both manifest dysbiosis as a result of decreases in evenness, microbial diversity, richness, and an increased Firmicutes/Bacteroidetes (F/B) ratio in the renin‐dependent form of hypertension in both essential hypertensive patients and animals .…”
Section: Introductionmentioning
confidence: 99%